Dehydrogenation catalyst as well as preparation method and application thereof
By plasma treatment of the support and loading precious metals, a dehydrogenation catalyst is prepared, which solves the problem of low cycle stability of the existing catalyst, improves catalytic activity and cycle stability, and achieves an efficient dehydrogenation reaction.
Patent Information
- Application Number
- CN202411952782.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The circulation stability of existing dehydrogenation catalysts has dramatically decreased after multiple cycles, limiting their application in organic liquid hydrogen storage materials.
By plasma treatment of the support and then loading precious metals, a dehydrogenation catalyst is prepared and applied to organic liquid hydrogen storage materials, thereby improving the cycle stability of the dehydrogenation reaction.
The catalytic activity of the dehydrogenation catalyst and the cycle stability during multiple catalysis are improved, the dispersion effect of precious metals is enhanced, the agglomeration of precious metals is avoided, the preparation process is simplified, and the cost is reduced.
Smart Images

Figure CN119793449A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of dehydrogenation catalysts, and in particular to a dehydrogenation catalyst and a preparation method and application thereof. Background Art
[0002] As a highly promising green fuel and energy carrier, the application of hydrogen is limited by the efficiency and safety of storage and transportation. Commonly used hydrogen storage technologies include high-pressure gaseous hydrogen storage, low-temperature liquid hydrogen storage and organic liquid hydrogen storage. Among them, organic liquid hydrogen storage uses organic matter as a hydrogen storage carrier to achieve the storage and release of hydrogen through hydrogenation and dehydrogenation reactions. It has the advantages of high hydrogen storage density and good safety.
[0003] At present, when organic liquid hydrogen storage materials are used, they are often used in conjunction with catalysts for dehydrogenation reactions. Carbon nanotubes, as a carbon-based material with a unique structure, are widely used as catalyst carriers due to their excellent stability, high selectivity, and good metal-carrier interaction. However, the catalyst used has a problem of sharply reduced cycle stability after multiple cycles, which limits its application in actual production. Summary of the invention
[0004] In view of the deficiencies of the above-mentioned related technologies, the purpose of the present application is to provide a dehydrogenation catalyst and a preparation method and application thereof. The dehydrogenation catalyst is prepared by plasma treating the carrier and then loading precious metals, and applied to organic liquid hydrogen storage materials to improve the cyclic stability of the dehydrogenation reaction.
[0005] In the first aspect, the present application provides a method for preparing a dehydrogenation catalyst using the following technical solution: A method for preparing a dehydrogenation catalyst comprises the following steps: taking a carrier and subjecting it to plasma pretreatment with a reaction gas to obtain a pretreated carrier, and loading a noble metal on the pretreated carrier to obtain the dehydrogenation catalyst; The reaction gas includes one or more of an oxidizing gas, a reducing gas and a neutral gas.
[0006] Preferably, the reaction gas includes one or more of oxygen, hydrogen and an inert gas.
[0007] Preferably, the reaction gas comprises one or more of oxygen, hydrogen and argon. Preferably, the plasma pretreatment comprises the following steps: ionizing a reaction gas into plasma to react with the carrier, and the flow rate of the reaction gas is 5-15 mL / min.
[0008] Preferably, the flow rate of the reaction gas is 10 mL / min.
[0009] Preferably, the ionization voltage is 80-120V.
[0010] Preferably, the ionization voltage is 100V.
[0011] Preferably, the loading of precious metals comprises the following steps: mixing the pretreated carrier with a precursor and then subjecting the mixture to high temperature treatment.
[0012] Preferably, the temperature parameter of the high temperature treatment is 200-250° C., and the treatment time is 1-3 hours.
[0013] Preferably, the high temperature treatment is performed under a reducing atmosphere, and the reducing atmosphere is achieved by a mixed gas including hydrogen and argon.
[0014] Preferably, the flow rate of the mixed gas is 60-80 mL / min.
[0015] Preferably, the flow rate of the mixed gas is 70 mL / min.
[0016] Preferably, the carrier comprises one or more of carbon nanotubes and activated carbon nanotubes.
[0017] Preferably, the carrier is activated carbon nanotubes.
[0018] Preferably, the activated carbon nanotubes are prepared by the following steps: mixing carbon nanotubes, alkali and water, stirring and drying, then treating at 750-850° C. in an inert gas atmosphere, and finally neutralizing with acid, washing with water to neutrality, drying and grinding.
[0019] Preferably, the noble metal includes one or more of platinum and palladium.
[0020] Preferably, the noble metal is palladium.
[0021] Preferably, the precursor comprises aqueous ammonia and sodium chloropalladate.
[0022] Preferably, the mixing comprises mixing and stirring aqueous ammonia, sodium chloropalladate and the pretreated carrier.
[0023] In a second aspect, the present application provides a dehydrogenation catalyst using the following technical solution: A dehydrogenation catalyst is prepared by the above-mentioned dehydrogenation catalyst preparation method.
[0024] In a third aspect, the present application provides an application of a dehydrogenation catalyst in a dehydrogenation reaction of an organic liquid hydrogen storage material.
[0025] Preferably, the method comprises the following steps: mixing and heating the organic liquid hydrogen storage material, the dehydrogenation catalyst and a solvent.
[0026] Preferably, the solvent is mesitylene.
[0027] Preferably, the added amount of the dehydrogenation catalyst is 15-25wt% of the organic liquid hydrogen storage material.
[0028] Preferably, the added amount of the dehydrogenation catalyst is 20 wt % of the organic liquid hydrogen storage material.
[0029] Preferably, the organic liquid hydrogen storage material includes one or more of perhydronitrilopropylcarbazole, perhydronitriloethylcarbazole, 2-methylindole and quinoline.
[0030] Preferably, the organic liquid hydrogen storage material is perhydroaziridine carbazole.
[0031] In summary, the present application includes at least one of the following beneficial technical effects: 1. The present application treats the carrier by converting the reaction gas into plasma, and then loads the precious metal to obtain a dehydrogenation catalyst, regulates the type and quantity of functional groups on the surface of the carrier, and applies it to an organic liquid hydrogen storage material to improve the catalytic activity of the dehydrogenation reaction and the cycle stability during multiple catalysis; 2. The present application improves the dispersion effect of the precious metal by loading the precious metal onto the carrier, while avoiding the agglomeration of the precious metal as much as possible, thereby improving the catalytic effect of the dehydrogenation catalyst; 3. The preparation method of the present application, which converts the reaction gas into plasma to treat the carrier and then loads the precious metal, is simple to operate and low in cost, which is conducive to the production of dehydrogenation catalysts and the promotion of hydrogen production by organic liquid hydrogen storage materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a comparison diagram of the XRD diffraction patterns of Examples 2-4 and Comparative Example 2; Figure 2 It is a comparison diagram of the XRD diffraction patterns of Example 2, Examples 5-6 and Comparative Example 1; Figure 3 It is a comparison diagram of infrared spectra of Examples 2-4 and Comparative Example 2; Figure 4 It is a comparison diagram of the dehydrogenation rate-time curves of Examples 2-4 and Comparative Example 2; Figure 5 is a comparison diagram of the dehydrogenation rate-time curves of Example 2, Examples 5-6 and Comparative Example 1; Figure 6 is a comparison diagram of the dehydrogenation rate-time curves of 10 cycles of Example 1; Figure 7 is a comparison diagram of the dehydrogenation rate-time curves of 10 cycles of Example 2; Figure 8This is a comparison chart of the dehydrogenation rate-time curves of 10 cycles of Comparative Example 1. DETAILED DESCRIPTION
[0033] The present application is further described in detail below in conjunction with examples. The following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. In the following examples, if specific conditions are not specified, they are carried out according to normal conditions or conditions recommended by the manufacturer. The methods used are conventional methods known in the art unless otherwise specified, and the consumables and reagents used are commercially available unless otherwise specified. Unless otherwise specified, the professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the recorded content may also be applied to the present invention.
[0034] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0035] Example 1 Example 1 of the present application provides a dehydrogenation catalyst, which is prepared by the following steps: taking carbon nanotubes as carriers and laying them flat in a DBD discharge reactor, passing oxygen at a flow rate of 10 mL / min, controlling the output voltage to 100 V, closing the DBD discharge reactor after reacting for 2 minutes and stirring the carbon nanotubes evenly so that they are laid flat again in the DBD discharge reactor, cooling for 5 minutes and restarting the DBD discharge reactor, repeating the reaction and stirring three times and then taking them out to obtain a pretreated carrier. 0.495g of the pretreated carrier, 10mL of ammonia water (concentration of 1 mol / L) and 1mL of sodium chloropalladate (concentration of 5 mg / mL) were mixed and stirred for 12 hours and then placed in an 80°C constant temperature oil bath pot to evaporate for 3 hours, and then dried in an oven at 80°C to obtain a mixed powder. The mixed powder was placed in a tubular furnace, heated to 240°C at a heating rate of 5°C / min in an atmosphere of a mixed gas (10% volume fraction of hydrogen and 90% volume fraction of argon), kept the temperature constant and calcined for 2 hours, and ground after cooling to obtain a dehydrogenation catalyst.
[0036] Example 2 Example 2 of the present application provides a dehydrogenation catalyst. The difference between Example 2 and Example 1 is that the carrier of Example 2 is activated carbon nanotubes, and the activated carbon nanotubes are prepared by the following steps: 4g potassium hydroxide and 1g carbon nanotubes are added to 20mL ultrapure water, stirred thoroughly, and then placed in a 120°C constant temperature oil bath for evaporation, the remaining solid is transferred to a tubular furnace, and the temperature is increased to 800°C at a heating rate of 20°C / min under an argon atmosphere, and the temperature is maintained constant and calcined for 1h. Finally, the calcined product is added to ultrapure water and 1mol / L hydrochloric acid is added dropwise to neutralize it. It is repeatedly rinsed with ultrapure water until it is neutral, and then dried and ground to obtain activated carbon nanotubes.
[0037] Example 3 Example 3 of the present application provides a dehydrogenation catalyst. The difference between Example 3 and Example 2 is that in Example 3, hydrogen is introduced into the DBD discharge reactor.
[0038] Example 4 Example 4 of the present application provides a dehydrogenation catalyst. The difference between Example 4 and Example 2 is that in Example 4, argon gas is introduced into the DBD discharge reactor.
[0039] Example 5 Example 5 of the present application provides a dehydrogenation catalyst. The difference between Example 5 and Example 2 is that in Example 5, the output voltage of the DBD discharge reactor is controlled to be 80V.
[0040] Example 6 Example 6 of the present application provides a dehydrogenation catalyst. The difference between Example 6 and Example 2 is that in Example 6, the output voltage of the DBD discharge reactor is controlled to be 120V.
[0041] Comparative Example 1 Comparative Example 1 provides a dehydrogenation catalyst, which is prepared by the following steps: 0.495g of carbon nanotubes, 10mL of ammonia water (concentration of 1mol / L) and 1mL of sodium chloropalladate (concentration of 5mg / mL) are mixed and stirred for 12h, then placed in an 80°C constant temperature oil bath for evaporation for 3h, and then dried in an oven at 80°C to obtain a mixed powder. The mixed powder is placed in a tubular furnace, heated to 240°C at a heating rate of 5°C / min in an atmosphere of a mixed gas (10% volume fraction of hydrogen and 90% volume fraction of argon), the temperature is kept constant and calcined for 2h, and ground after cooling to obtain a dehydrogenation catalyst.
[0042] Comparative Example 2 Comparative Example 2 provides a dehydrogenation catalyst. The difference between Comparative Example 2 and Comparative Example 1 is that in Comparative Example 2, the carbon nanotubes are replaced by activated carbon nanotubes.
[0043] Test and Inspection (1) X-ray diffraction was performed on the dehydrogenation catalysts of Examples 2-6 and Comparative Examples 1-2, and a comparison of the XRD diffraction patterns of the same batch of Examples 2-4 and Comparative Example 2 was obtained as shown in the figure below: Figure 1 As shown (wherein Example 2 is marked as Pd / C-O2, Example 3 is marked as Pd / C-H2, Example 4 is marked as Pd / C-Ar and Comparative Example 2 is marked as Pd / C), the XRD diffraction pattern comparison diagram of Example 2, Examples 5-6 and Comparative Example 1 of the same batch is obtained as shown Figure 2As shown (wherein Example 5 is marked as Pd / C-80V, Example 2 is marked as Pd / C-100V, Example 6 is marked as Pd / C-120V and Comparative Example 1 is marked as Pd / Cu).
[0044] (2) The dehydrogenation catalysts of Examples 2-4 and Comparative Example 2 were tested by infrared spectroscopy to obtain a comparison of infrared spectra of Examples 2-4 and Comparative Example 2 of the same batch as shown in the figure below: Figure 3 As shown (wherein Example 2 is marked as Pd / C-O2, Example 3 is marked as Pd / C-H2, Example 4 is marked as Pd / C-Ar and Comparative Example 2 is marked as Pd / C).
[0045] (3) The dehydrogenation catalysts of Examples 2-6 and Comparative Examples 1-2 were applied to the organic liquid hydrogen storage material, and the dehydrogenation rate was detected. The specific steps were as follows: 0.2 g of dehydrogenation catalyst, 1.0 g of perhydronitriloylcarbazole and 3.0 g of mesitylene were added to a three-necked round-bottom flask, placed in an oil bath at 180°C, and the speed was adjusted to 200 r / min to perform a dehydrogenation reaction. Samples were taken at regular intervals and detected and analyzed using a gas chromatograph to obtain a comparison of the dehydrogenation rate-time curves of the same batch of Examples 2-4 and Comparative Example 2 as shown in the figure. Figure 4 As shown (wherein Example 2 is marked as Pd / C-O2, Example 3 is marked as Pd / C-H2, Example 4 is marked as Pd / C-Ar and Comparative Example 2 is marked as Pd / C), the dehydrogenation rate-time curve comparison of Example 2, Examples 5-6 and Comparative Example 1 of the same batch is obtained as shown in Figure 5 As shown (wherein Example 5 is marked as Pd / C-80V, Example 2 is marked as Pd / C-100V, Example 6 is marked as Pd / C-120V and Comparative Example 1 is marked as Pd / Cu).
[0046] (4) The dehydrogenation catalysts of Example 1, Example 2 and Comparative Example 1 are applied to organic liquid hydrogen storage materials, and a cyclic dehydrogenation experiment is carried out. The specific steps are as follows: 0.2 g of dehydrogenation catalyst, 1.0 g of fully hydrogenated aziridine carbazole and 3.0 g of mesitylene are added to a three-necked round-bottom flask, placed in an oil bath at 180°C, and the speed is adjusted to 200 r / min to carry out a dehydrogenation reaction. After the reaction is completed, the dehydrogenation catalyst is rinsed with mesitylene until there is no fully hydrogenated aziridine carbazole and its dehydrogenation product in the rinsed mesitylene. The same dehydrogenation experiment is repeated 10 times using the rinsed catalyst. The comparison diagram of the dehydrogenation rate-time curve of 10 cycles of Example 1 is shown as follows. Figure 6 As shown, the dehydrogenation rate-time curve comparison diagram of 10 cycles of Example 2 is as follows Figure 7 As shown, the dehydrogenation rate-time curve comparison of 10 cycles of comparative example 1 is shown in Figure 8 shown.
[0047] Results Analysis The following combination Figure 1-8 , describe this application in detail.
[0048] Reference Figure 1 and Figure 2 , Figure 1 The effect of plasma treatment of different reaction gases on the crystal structure and phase composition of dehydrogenation catalysts during their preparation is studied. Figure 2 The effect of plasma treatment with different output voltages on the crystal structure and phase composition of the dehydrogenation catalyst during its preparation process was investigated. The results showed that the palladium nanoparticles were evenly dispersed on the carbon nanotubes, resulting in a weaker diffraction peak intensity. However, the graphite diffraction peaks corresponding to the carbon nanotubes before and after treatment did not change significantly, and the original crystal phase structure was still maintained, proving that cold plasma treatment had no significant effect on the crystal structure of carbon nanotubes.
[0049] Reference Figure 3 , Figure 3 The effect of plasma treatment of different reaction gases on the surface groups of dehydrogenation catalysts during the preparation process was studied. The results showed that after plasma treatment with oxygen as the reaction gas, the surface of carbon nanotubes contained more C=O double bond groups such as ester groups, carboxyl groups or carbonyl groups and CO single bond groups, which enhanced the interaction between the active metal palladium and the carrier.
[0050] Reference Figure 4 and Figure 5 , Figure 4 The effect of plasma treatment of different reaction gases on the dehydrogenation rate of dehydrogenation catalysts used in the dehydrogenation of organic liquid hydrogen storage materials during the preparation process is studied. Figure 5 The effect of plasma treatment with different output voltages on the dehydrogenation rate of the dehydrogenation catalyst when it is used in the dehydrogenation of organic liquid hydrogen storage materials during the preparation process is shown in Figure 2. The results show that compared with Comparative Examples 1-2, when Examples 2-6 are used in the dehydrogenation of organic liquid hydrogen storage materials, the dehydrogenation rate and dehydrogenation rate are significantly improved, and when oxygen is used as the reaction gas, the dehydrogenation rate of the dehydrogenation catalyst of Example 2 in 300 minutes reaches 5.43wt%, achieving complete hydrogen release. Figure 3-5 , indicating that when preparing the dehydrogenation catalysts as in Examples 2-6, treating the carrier with plasma and then loading the precious metal is beneficial to improving the dehydrogenation rate and dehydrogenation rate of the dehydrogenation catalyst when used in the dehydrogenation of organic liquid hydrogen storage materials. Furthermore, using oxygen as the reaction gas to perform plasma treatment on the carrier enhances the interaction between the active metal palladium and the carrier, further improving the catalytic effect of the dehydrogenation catalyst as in Example 2.
[0051] Reference Figure 6-8, when the dehydrogenation catalyst of comparative example 1 is applied to the dehydrogenation of organic liquid hydrogen storage materials, the dehydrogenation rate drops significantly from the second cycle, when the dehydrogenation catalyst of embodiment 1 is applied to the dehydrogenation of organic liquid hydrogen storage materials, after 10 cycles, the dehydrogenation rate drops slightly, but is still much higher than the dehydrogenation catalyst of comparative example 1; and when the dehydrogenation catalyst of embodiment 2 is applied to the dehydrogenation of organic liquid hydrogen storage materials, after 10 cycles, the dehydrogenation rate remains at the same level as the first time. This indicates that plasma treatment of the carrier with a reaction gas is beneficial to improving the cyclic stability of the dehydrogenation catalyst when applied to the dehydrogenation of organic liquid hydrogen storage materials. Furthermore, using activated carbon nanotubes as carriers and plasma treatment of the carrier with a reaction gas have a synergistic effect in improving the cyclic stability of the dehydrogenation catalyst when applied to the dehydrogenation of organic liquid hydrogen storage materials.
[0052] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a dehydrogenation catalyst, characterized in that: The following steps are involved: Taking a carrier and subjecting it to plasma pretreatment with a reaction gas to obtain a pretreated carrier, and loading a noble metal on the pretreated carrier to obtain the dehydrogenation catalyst; The reaction gas includes one or more of an oxidizing gas, a reducing gas and a neutral gas.
2. The method for preparing a dehydrogenation catalyst according to claim 1, characterized in that: The plasma pretreatment comprises the following steps: ionizing a reaction gas into plasma to react with the carrier, and the flow rate of the reaction gas is 5-15 mL / min.
3. The method for preparing a dehydrogenation catalyst according to claim 2, characterized in that: The ionization voltage is 80-120V.
4. The method for preparing a dehydrogenation catalyst according to claim 1, characterized in that: The method of loading the precious metal comprises the following steps: mixing the pretreated carrier with a precursor and then subjecting the mixture to high temperature treatment.
5. The method for preparing a dehydrogenation catalyst according to claim 4, characterized in that: The temperature parameters of the high temperature treatment are 200-250° C. and the treatment time is 1-3 hours.
6. The method for preparing a dehydrogenation catalyst according to claim 1, characterized in that: The carrier includes one or more of carbon nanotubes and activated carbon nanotubes.
7. The method for preparing a dehydrogenation catalyst according to claim 1, characterized in that: The noble metal includes one or more of platinum and palladium.
8. A dehydrogenation catalyst, characterized in that: The dehydrogenation catalyst is prepared by the preparation method of the dehydrogenation catalyst according to any one of claims 1 to 7.
9. Use of a dehydrogenation catalyst as claimed in claim 8 in a dehydrogenation reaction of an organic liquid hydrogen storage material, characterized in that: The following steps are involved: The organic liquid hydrogen storage material, the dehydrogenation catalyst and the solvent are mixed and heated.
10. The use of a dehydrogenation catalyst according to claim 9, characterized in that: The addition amount of the dehydrogenation catalyst is 15-25wt% of the organic liquid hydrogen storage material.
Citation Information
Patent Citations
Pt / C catalyst and preparation method thereof
CN110327919A
Nano-metal catalyst for hydrogenation and dehydrogenation of liquid organic hydrogen storage material as well as preparation method and application of nano-metal catalyst
CN116060137A
Dehydrogenation catalyst, hydrogen production system, and hydrogen production method
JP2017148749A
Cited By
Carbon-supported platinum-nickel catalyst as well as preparation method and application thereof
CN121097109A